Prepubertal Ovariectomy Exaggerates Adult Affective Behaviors and Alters the Hippocampal Transcriptome in a Genetic Rat Model of Depression - Raghavan, Neha S.; Chen, Hao; Schipma, Matthew; Luo, Wendy; Chung, Sarah; Wang, Lei; Redei, Eva E. (Frontiers in Endocrinology, 2018)
Major depressive disorder (MDD) is a debilitating illness that affects twice as many women than men post-puberty. This female bias is thought to be caused by greater heritability of MDD in women and increased vulnerability induced by female sex hormones. We tested this hypothesis by removing the ovaries from prepubertal Wistar Kyoto More Immobile (WMI) females, a genetic animal model of depression, and its genetically close control, the WKY Less Immobile (WLI). In adulthood, prepubertally ovariectomized (PrePubOVX) animals and their sham-operated controls were tested for depression- and anxiety-like behaviors, using the routinely employed forced swim and open field tests, respectively, and RNA-sequencing was performed on their hippocampal RNA. Our results confirmed that the behavioral and hippocampal expression changes that occur after prepubertal ovariectomy are the consequences of an interaction between genetic predisposition to depressive behavior and ovarian hormone regulated processes. Lack of ovarian hormones during and after puberty in the WLIs led to increased depression-like behavior. In WMIs, both depression- and anxiety- like behaviors worsened by prepubertal ovariectomy. The unbiased exploration of the hippocampal transcriptome identified sets of differentially expressed genes (DEGs) between the strains and treatment groups. The relatively small number of hippocampal DEGs resulting from the genetic differences between the strains confirmed the genetic relatedness of these strains. Nevertheless, the differences in DEGs between the strains in response to prepubertal ovariectomy identified different molecular processes, including the importance of glucocorticoid receptor-mediated mechanisms, that may be causative of the increased depression-like behavior in the presence or absence of genetic predisposition. This study contributes to the understanding of hormonal maturation-induced changes in affective behaviors and the hippocampal transcriptome as it relates to genetic predisposition to depression.